Pelaksanaan P5 Pada Dimensi Kreatif Melalui Kegiatan Market Day Dalam Menanamkan Karakter Entrepreneurship Siswa - Nurmartha, Doci; Jono, Ali Akbar; Lukman, Lukman (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to determine the implementation of P5 in the creative dimension through market day activities in instilling the character of entrepreneurship students in MIN 2 Central Bengkulu. Type of research in the form of field research (file research), with a descriptive qualitative approach. Data collection techniques, namely, observation, interviews, and documentation. Data analysis techniques are, data reduction, data presentation and conclusion. For data validity techniques include credibility test, transferability test, dependability test, and Confirmability test. The results obtained from this study showed that: 1) the process of implementation of P5 on the creative dimension through market day activities in instilling the character of entrepreneurship students in MIN 2 Bengkulu Tengah through three stages of preparation, planning, implementation, and evaluation stages. 2) The Teacher's efforts in instilling the character of the spirit of entrepreneurship through student market day activities in MIN 2 Central Bengkulu, namely teaching some characteristics of the spirit of entrepreneurship to students, such as teaching creative, responsible, confident, and how to manage finances. 3) patterns or strategies in instilling entrepreneurship character education of students in MIN 2 Bengkulu Tengah, namely entrepreneurship project-based learning, learning through role models and supportive environments.